ANALISIS PENERAPAN AKUNTANSI LINGKUNGAN PADA PROGRAM KONSERVASI LINGKUNGAN PT PUPUK KALTIM DI BONTANG - Zulfikar Zulfikar; Chottam Chottam; Widiya Windar Wati (Politeknik Negeri Samarinda, 2020)
The purpose of this research is to know the application of environmental accounting based on accounting treatment (measurement, recognition, presenting, and disclosing) and conformity with existing rules at PT Pupuk Kaltim. This research is a qualitative descriptive research, data is collected from interview with the company’s employee and the people that live close to the area of production which assisted by recording equipment which helps as crosscheck media. The methods analysis is using PSAK No.1. The result of this research showed that the company has spending money for environmental cost as an effort to prevent the damaged of environmental cause by the production procces of company. The company has measure the environmental cost with rupiah monetary units reffering to the realization of the previous period costs by the amount of the cost incurred. The company recognizes the environmental cost when it benefited from it even though cash has not been spend yet and presented with accounts related to the production procces, it is the cost of revenue and general and administration expenses in the company’s income statement. The environmental cost has not dislosure yet in notes to the consolidated financial statements, this causes the posts in financial statements do not indicated the existence of environmental cost that has been incurred by the company. The company also has not made additional report yet related to the environmental cost based on PSAK No.1 about presentation of financial statement. Keywords: Environmental Accounting, Environmental Conservation, Environmental Cost.